CHARACTERISTICS AND MANAGEMENT OF GONORRHEA : A TEN YEARS SYSTEMATIC REVIEW - Ramadhani Bara, Rahmah; Dzakwan Bara, Dary; Rahmadita Putri Hendry, Uray Anifa (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Neisseria gonorrhoeae, an obligate human pathogen, is a sexually transmitted disease that causes consequential worldwide morbidity both in resource-abundant and resource-limited nations, and its diagnosis and treatment require costly expenditures annually. Like other sexually transmitted infections (STIs), gonorrhea disproportionately impacts young adult populations. The aim: The aim of this study to show about characteristics and management of gonorrhea. Methods: By the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. This search approach, publications that came out between 2014 and 2024 were taken into account. Several different online reference sources, like Pubmed, SagePub, and Google Scholar were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Result: In the PubMed database, the results of our search get 51 articles, whereas the results of our search on SagePub get 551 articles, on Google Scholar 2410 articles. Records remove before screening are 1219, so we get 1793 articles fos screening. After we screened based on record exclude, we compiled a total of 12 papers. We included five research that met the criteria. Conclusion: The management of N. gonorrhoeae infections was compromised by a low rate of examining sexual partners, females and testing extragenital specimens, screening for HIV, compliance to follow-up visits, access to nucleic acid amplification tests, and receiving questionable or even obsolete antimicrobial treatment. Therefore, more accurate and comprehensive management of gonorrhea is urgently needed.